THE EFFECT OF LEADERSHIP, MOTIVATION AND THE WORK ENVIRONMENT ON EMPLOYEE PERFORMANCE AT PT. TANJUNG SELATAN MAKMUR JAYA - Firdaus, Firdaus (DiE: Jurnal Ilmu Ekonomi dan Manajemen, 2021)
This study aims to: (1) Test the leadership of a positive andsignificant effect on employees; (2) Testing motivation has a positive andsignificant effect on employees; (3) Testing the work environment has apositive and significant effect on employees; (4) Testing leadership,motivation and work environment has a positive and significant effect onemployees. This type of quantitative research with direct survey methoduses a questionnaire with a Likert scale measurement. Data analysis usingmultiple linear regression, hypothesis testing and determinationcoefficients were assisted with SPSS version 24. The results showed that:(1) Leadership had a positive and significant effect on employees at PT.Tanjung Selatan Makmur Jaya; (2) Motivation has a positive andsignificant effect on employees at PT. Tanjung Selatan Makmur Jaya; (3)The work environment has a positive and significant effect on employeesat PT. Tanjung Selatan Makmur Jaya, thus the third hypothesis isaccepted; (4) Leadership, motivation and work environment have apositive and significant effect on employees at PT. Tanjung SelatanMakmur Jaya is proven by the significance test result of 0,000 <0.05 thusthe fourth hypothesis is accepted..Keywords: Leadership, Motivation; Work Environment; EmployeePerformance.